2017
DOI: 10.1007/s10549-017-4177-9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying socio-demographic and clinical characteristics associated with medication beliefs about aromatase inhibitors among postmenopausal women with breast cancer

Abstract: Medication necessity and concern beliefs were associated with a definable subset of patients who may be at higher risk for non-persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
2
18
1
2
Order By: Relevance
“…This research is among the first to show how patients' beliefs in the necessity of their medications decline when medications are withdrawn by the physician. Consistent with several cross‐sectional studies of beliefs about different medication types, we found that treatment interruptions may give rise to concerns that oral oncolytic agents are no longer managing their disease. At least 2 lines of explanation might be pursued.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This research is among the first to show how patients' beliefs in the necessity of their medications decline when medications are withdrawn by the physician. Consistent with several cross‐sectional studies of beliefs about different medication types, we found that treatment interruptions may give rise to concerns that oral oncolytic agents are no longer managing their disease. At least 2 lines of explanation might be pursued.…”
Section: Discussionsupporting
confidence: 87%
“…The Beliefs about Medicines Questionnaire (BMQ) is grounded in social cognition as expressed through the health belief model and assesses patients' positive outcome expectancy (benefits from treatment) and the accompanying concerns regarding the use of medications and their interference with daily activities . Patients' scores on the necessity and concerns subscales have been found to be associated with their levels of adherence as well as with their sex, symptom reports, duration of treatment, number of medications, and depression …”
Section: Introductionmentioning
confidence: 99%
“…However, if cancer‐related symptoms are relieved by the OA medication or patients do not experience symptoms that they associate with the OA medication, the strength of the negative medication beliefs would likely weaken. The positive component of medication beliefs has not been reported to be influenced by cancer treatment‐related assaults (Heisig et al, ; Salgado et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Positive medication beliefs represent the beliefs that the patient will benefit from medication. Positive medication beliefs are less likely to be associated with treatment‐related assaults (Heisig et al, ; Salgado et al, ) and thus are hypothesised to be more stable over time. However, positive medication beliefs can change and strengthen as patients confirm medication efficacy or weaken if a patient experiences a permanent physician‐directed OA stoppage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation